Risk factors for mild cognitive impairment in type 2 diabetes: a systematic review and meta-analysis - Zhao, Yi; Wang, Hanlin; Tang, Guanghao; Wang, Leilei; Tian, Xuewen; Li, Ran (Frontiers in Endocrinology, 2025)
BackgroundMild Cognitive Impairment (MCI), a transition between normal aging and dementia, is linked to higher dementia risk and potential reversibility. Type 2 Diabetes Mellitus (T2DM), affecting over 537 million adults worldwide, increases susceptibility to MCI, with higher cognitive decline prevalence in diabetic populations. Previous meta-analyses focused on isolated factors, neglecting multidimensional interactions. This study synthesizes T2DM-MCI risk factors across clinical, lifestyle, and biochemical dimensions to support early identification and intervention of cognitive dysfunction in T2DM populations.Materials and MethodsThis systematic review and meta-analysis, following PRISMA guidelines, searched five databases for articles published from January 1, 2014, to December 31, 2024. Studies were screened based on predefined criteria, with data extracted independently by two researchers. Quality was assessed using Newcastle-Ottawa Scale (NOS) and Joanna Briggs Institute (JBI) tools. Data were analyzed using RevMan software, with odds ratio (OR) and 95% CI as effect size measures. Heterogeneity was assessed using I² statistics, and subgroup analyses were conducted for factors with ≥10 studies.Results30 studies with 10,469 participants were included. Prevalence rate of MCI in T2DM was 44.1%. Significant associations were found between T2DM-MCI and age (OR = 1.06, P = 0.01), female sex (OR = 1.23, P = 0.05), diabetes duration (OR = 1.07, P = 0.03), education (OR = 0.82, P = 0.0001), smoking (OR = 1.44, P = 0.003), hypertension (OR = 2.25, P < 0.001), cardiovascular disease (CVD) (OR = 2.61, P < 0.001), glycated hemoglobin (HbA1c) (OR = 1.33, P = 0.001), and homeostasis model assessment of insulin resistance (HOMA-IR) (OR = 1.95, P = 0.02).ConclusionThis meta-analysis identifies advanced age (≥60 years), female sex, prolonged Diabetes duration (8–9 years), elevated HbA1c (>9%), and low education (≤6 years) as key predictors of MCI in T2DM, with significant dose-response relationships. Vascular comorbidities, insulin resistance, and inflammatory markers further exacerbate risks. Clinical priorities include rigorous glycemic control (HbA1c <7%), targeted cognitive screening for high-risk subgroups, and multidisciplinary care for patients with microvascular complications. However most of the studies included in this study come from Chinese people, so the generalization of the results may be limited.Systematic review registrationhttps://www.crd.york.ac.uk/prospero, identifier CRD420250637336.